What just happened? Impact of on-campus activities suspension on pharmacy education during COVID-19 lockdown - A students' perspective - Majid Ali; Moayad Allihyani; Akrm Abdulaziz; Safwan Alansari; Sultan Faqeh; Ahmad Kurdi; Abdulrahman Alhajjaji (Elsevier, 2021)
Introduction: COVID-19 pandemic induced lockdown, suspending all on-campus educational activities in the Kingdom of Saudi Arabia (KSA), compelling to continue the education online. We explored pharmacy students' perspective on its impact on their learning. Methods: A Twitter chat was organized on three consecutive days, after final examinations, inviting all pharmacy students in KSA to participate. Day 1 chat included 11 questions regarding learning and assessment, Day 2 chat included six questions about online examinations and six questions about technology use, Day 3 chat included six questions related to lessons learnt from the learning experiences during the lockdown. The questions were validated and piloted before the chat. The responses were copied, reviewed to remove any confidential information, and thematically analyzed by two teams of research students independently. Results: During the three-day chat, 790 responses were received in total. Thematic analysis generated 944 codes which were categorized into 43 subthemes. These subthemes were further categorized into six main themes: 'facilitators for online education', 'barriers for online education', 'online versus onsite education', 'role of technology in online education', 'suggestions for improving online education' and 'long-term impact of online education during lockdown'. Participants highlighted several facilitators and barriers which affected their education during the lockdown, compared online education with onsite education, and provided suggestions for improving online education based on their learning experiences during the lockdown. Conclusion: As COVID-19 pandemic and its repercussions are expected to last longer, pharmacy colleges and academic staff will find these findings useful to prepare for the coming years, ensuring pedagogical and accreditation standards.